الدراسة التحليلية لألفاظ التضادات في سورة المعارج على النظرة علي الخلي: STUDI ANALISIS LAFADH ANTONIM PADA Q.S AL MA'ARIJ PERSPEKTIF M. ALI AL-KHULI - Eli ELI SAFITRI; Siti Norazizah; Nur Ila Ifawati (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2023)
Verses of the Qur'an as a guide for Muslims in organizing and applying the life of the world and the Hereafter. Therefore the Qur'an uses the language of the ummah in which they live. Prophet Muhammad was chosen as an envoy to spread Islam with the guidelines of the Qur'an according to the language used. Understanding the Qur'an is not enough to read it, even though every reading has a reward. Moreover, understanding the Qur'an's language must receive more attention to get a thorough understanding of all aspects of the instructions intended for this whole nature. This linguistic understanding such as antonyms in the Qur'an or dilalah in Q.S al-Ma'arij will be discussed in this article to look for antonyms in the surah based on the range of meanings and types of antonyms of the semantic perspective of AL-Khulli. The method in this paper uses al-Khulli semantics by racing on his theory of nine types of antonyms in Arabic. However, in Q.S Ma'arij. From his conclusion there are thirteen types of antonyms namely: Binary (تضاد حاد ), vertical antonymy (تضاد عمودي), Affinity (تضاد انتسابي ), Graded (ضاد متدرج), Convergence (تضاد عكس). Keywords : Antonyms, Linguistics, Sentences, al-Ma'arij